2021- IFAD-UE/CCAFS CSA Monitoring: Kaffrine Climate-Smart Village (Senegal) - Bonilla-Findji, Osana; Eitzinger, Anton; Ouedraogo, Mathieu; Zougmoré, Robert B.; Läderach, Peter R.D.; Sall, Moussa (2021)
This dataset contains the files produced in the implementation of the “Integrated Monitoring Framework for Climate-Smart Agriculture” in the Kaffrine Climate Smart Village (Senegal) in February 2021 This monitoring framework developed by CCAFS is meant to be deployed annually across the global network of Climate-Smart Villages to gather field-based evidence by tracking the progress on: adoption of CSA practices and technologies, as well as access to climate information services and their related impacts at household level and farm level